Past, present and future of the “responsibility to protect”: abumpy journey - Fernandes, Vítor Manuel Ramon (2017)
The aim of this article is to study the “Responsibility to Protect”, its evolution since 2000 and what can be expected for its future. Concurrently, the paper takes into account the need to protect populations, victims of certain types of aggression and to preserve the international order. Major criticisms of this doctrine are highlighted, as well as some of its impacts on the international community and, significantly, some of the difficulties that have arisen during its development – a process that has been controversial and troubled. Some of the main risks and uncertainties that affect its future are investigated, considering that a set of emerging countries who do not agree with the Western liberal order intends to be more active in international affairs. The fundamental argument is that the future of this doctrine might continue to be troubled and full of uncertainties. Thus, for RtoP to evolve in a favourable way, it will be necessary, on the one hand, that the members of the Security Council of the United Nations engage in genuine multilateral cooperation in order to safeguard the changes taking place in the international order; and, on the other hand, that the States consider such crimes to be an essential issue of international security and part of their interests.